Edible film production from chia seed mucilage: Effect of glycerol concentration on its physicochemical and mechanical properties. (5th October 2015) - Dick, Melina; Costa, Tania Maria Haas; Gomaa, Ahmed; Subirade, Muriel; Rios, Alessandro de Oliveira; Flôres, Simone Hickmann
Graphical abstract: Highlights: Edible films from chia mucilage were successfully produced and characterized. WVP, EB, WS of chia mucilage films increased as glycerol concentration increased. The films showed high solubility, transparency, and UV barrier properties. Chia mucilage can be used as edible packaging or coating material. Abstract: This study investigated the physicochemical and mechanical properties of a novel edible film based on chia mucilage (CM) hydrocolloid. CM (1% w/v) films were prepared by incorporation of three concentrations of glycerol (25%, 50%, and 75% w/w, based on CM weight). As glycerol concentration increased, water vapor permeability (WVP), elongation at break (EB), and water solubility of CM films increased while their tensile strength (TS), and Young's modulus (YM) decreased significantly ( p < 0.05). CM films containing a high concentration of glycerol were slightly reddish and yellowish in color but still had a transparent appearance. CM films exhibited excellent absorption of ultraviolet light, and good thermal stability. The scanning electron micrographs showed that all CM films had a uniform appearance. This study demonstrated that the chia mucilage hydrocolloid has important properties and potential as an edible film, or coating.